The factors influencing purchase decision of residential properties in Bandar Seri Iskandar, Perak / Nur Raihan Murtadza and Nor Aini Salleh - Murtadza, Nur Raihan; Salleh, Nor Aini (2018)
The objective of this study is to identify the factors influencing the purchase decision of residential properties in Bandar Seri Iskandar, District of Perak Tengah, Perak. A conceptual framework was developed based on literature review of previous studies and was then tested on a sample of 110 respondents. The data for this study was collected by using a close-ended questionnaire based on the stratified sampling and convenience sampling methods. Relative Importance Index and Descriptive Analysis were used to analyse the data collected. The study found that the major factor influencing the purchase decision of residential properties is neighbourhood (0.7523), followed by concept and building features (0.7391), financial (0.7296), location (0.7207), type of land ownership (0.7184), developer reputation (0.7013), demographic (0.6727), and socio-cultural (0.5474). The study is expected to provide more insight into the consistency of factors influencing purchase decision of residential properties.